La demanda y la contestación en el arbitraje - Castillo Freyre, Mario (2013)
In this Article, the authors examine different institutions such as lawsuits, answers, counterclaim, the possibility of extending each of these, consolidation, among others. We must not lose sight of the critical aspect this essay addresses: apparently, the way the Peruvian Arbitration Law has not dealt with some of such institutions in the most appropriate manner, as we will see.